Epichromatin is conserved in Toxoplasma gondii and labels the exterior parasite chromatin throughout the cell cycle - Vanagas, Laura (2013)
Toxoplasma gondii is an Apicomplexan intracellular protozoan parasite responsible for Toxoplasmosis, a disease with considerable medical and economic impact worldwide. T. gondii cells never lose the nuclear envelope and their chromosomes do not present a higher order level of condensation during mitosis. Here, we tested the murine monoclonal antibody PL2-6, which labels epichromatin, a conformational chromatin epitope based on DNA+H2As and H2Bs, in T. gondii cultured on fibroblast cells. This epitope is present on the exterior chromatin surface of interphase nuclei and on the periphery of metaphasic chromosomes in higher eukaryotes. PL2-6 reacted with T. gondii H2As and H2Bs histones in Western blot assays. Besides, the antibody reacted with the nuclear fraction of tachyzoites, as a single band coincident with H2B histone. In the T. gondii tachyzoite stage, PL2-6 also had peripheral nuclear localization, as observed by epifluorescence/confocal microscopy and also immunoelectron microscopy. Confocal analysis showed that epichromatin is slightly polarized to one face of the parasite exterior chromatin surface. In replicating tachyzoites, PL2-6 also labels the exterior chromatin surface, covering the face of both segregating nuclei, facing the plasma membrane of the mother cell. The possible role of epichromatin in T. gondii is discussed.